The Influence Analysis of Industry Attractiveness and Capabilities on the Transient Competitive Advantage of Micro, Small and Medium Enterprises in Indonesia - Hermina, Nurul; Roespinoedji, Djoko; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The business of small and medium enterprises in Indonesia (SME; Indonesian: Usaha Kecil Menengah/UKM) in Indonesia has had positive impacts on the economic growth of the people. The analysis of competitive advantage of micro, small, and medium enterprises (MSME, Indonesian: Usaha Mikro, Kecil, dan Menengah/UMKM) in Indonesia can be the basis for developing MSME/UMKM businesses by finding dominant factors explaining the competitive advantage through the analysis process. This research is aimed to explain the influence of industry attractiveness and business capability on the competitive advantage of MSME/UMKM in Indonesia. The research method applied is descriptive-verifiable with a survey approach. Through the online survey, there were 52 MSME data points, with those who chose SME or the people with a higher position than them as the observed units. The second-order structural equation modelling is used to prove the research hypothesis that industry attractiveness and business capability influence the competitive advantage of MSME/UMKM. The second-order modelling applied in this research helps to find the most dominant dimension explaining every research variable and also the most important indicator constructing every dimension used to measure the research variable. The second-order method with repeated measurement approach is easy to apply with the help of plspm packages on an open source program R. This method finds that all dimensions and indicators are valid with a standardized loading factor value greater than the minimum limit determined by various literatures, and the most influential variable in the competitive advantage of MSME/UMKM is business capability.